1971
DOI: 10.1099/00221287-65-2-153
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Bacteriophage   DNA After Adsorption by Haemophilus influenzae

Abstract: S U M M A R YRadioactively labelled coliphage h DNA is rapidly and irreversibly bound by competent bacteria of certain cultures of Haemophilus influenzae. The extent of adsorption in the presence of excess cells was always between 30 and 40 % of the DNA added. Bound DNA was rather resistant against degradation to acid-soluble products but the biological activity was completely lost after 60 min. incubation. Reisolated phage h DNA always banded in CsCl gradient centrifugation at a position characteristic for do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1971
1971
1984
1984

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…influenzae differ in the ability to take up X DNA (13); modification systems specified by episomal elements might be expected to differ in different laboratory strains of the same organism. Such differences might also account for the quantitative differences among strains observed by Newman and Stuy (13) and ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…influenzae differ in the ability to take up X DNA (13); modification systems specified by episomal elements might be expected to differ in different laboratory strains of the same organism. Such differences might also account for the quantitative differences among strains observed by Newman and Stuy (13) and ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations of this phenomenon can be based on either (i) reduced uptake of the heterospecific deoxyribonucleic acid (DNA), (ii) the presence of so-called restriction enzymes (32) in the recipient that destroy the genetic integrity of adsorbed nonmodified DNA either before or after integration, or (iii) the lack of homology between donor and recipient DNA. Although competent Haemophilus influenzae Rd cells show a reduced uptake of unrelated foreign DNA (15,28), the uptake of heterologous Haemophilus parainfluenzae DNA appears to be normal (18,34). Moreover, the molecular fate of this DNA is comparable to that of homologous DNA after uptake (3,18,34,36).…”
mentioning
confidence: 99%
“…The fact that breakdown may occur outside the cell argues against such a view unless DNA integration occurs at the cell surface. The greatly reduced degradation of adsorbed heterologous DNA (Newman & Stuy, 1971) suggests that it may be. We believe, however, that studies such as the ones reported here and by Newman & Stuy (1971) cannot give us a clear answer since they employ different DNAs.…”
Section: Discussionmentioning
confidence: 99%